Perhitungan Kapasitas Kolam Retensi Rumah Susun Dosen Politeknik PU - Nicko Fadhil Muhammad; Aprillya Trihartati; Pipit Skriptianata P.P (Jurnal Talenta Sipil, 2026)
Water conservation utilizing rainwater is very effective and efficient both in the rainy season and in the dry season. The construction of this lecturer housing must be supported by a good drainage system so as not to increase the burden of water runoff to the surrounding area. Problems that can be formulated include: what is the flood discharge of the return period Q2, Q5 and Q10 before and after the construction of the Rusun Dosen Polythecnic PU, how long can the retention pond and other water structures accommodate the flood discharge in the area, what alternatives can be implemented if the capacity of the retention pond and other structures cannot accommodate the flood discharge in the area. The purpose of this study is to analyze the flood discharge of the return period Q2, Q5 and Q10 before and after the construction. Analyze water structures that can accommodate flood discharge. Analyze alternatives that can be applied. The methodology used is data collection, data analysis (maximum rainfall, rainfall distribution, flood discharge) and calculation of the capacity of water structures. The conclusions obtained are: the potential flood discharge of existing conditions is 0.119 m3/sec, the potential flood discharge after the construction is 0.303 m3/sec, there is an increase in flood discharge of 0.184 m3/sec, the capacity of water structures: retention ponds can accommodate flood discharge of 1,408.53 m3, RWT can accommodate flood discharge of 92.4 m3, infiltration wells can accommodate flood discharge of 25.12 m3, drainage channels can accommodate flood discharge of 143.2 m3. The total capacity of the retention pond and other water structures will be full if it rains for 2.52 hours. This does not meet SNI 03-3424-1994 standards. The recommendation is to enlarge the channel dimensions